SAT0023 The Association Between Adipokines Levels, Insulin Resistance and Inflammation in Patients with Early Rheumatoid Arthritis. (9th June 2015) - Kondratyeva, L.; Gorbunova, Y.; Popkova, T.; Avdeeva, A.; Aleksandrova, E.; Novikov, A.; Nasonov, E.
Abstract : Background: Obesity may pose negative impact on the development and progression of rheumatoid arthritis (RA). The adipose tissue is an active endocrine organ that synthesizes adipokines (adiponectin, leptin, etc.). A association between adipokines levels and markers of inflammation are widely discussed. Objectives: To examine the correlation between adipokins synthesis and levels of inflammatory cytokines in patients with early RA. Methods: The study included 27 early RA patients (criteria ACR/EULAR, 2010), 56 [46; 64] years old, with median disease duration 8 [6, 15] months. The majority of pts were seropositive for IgM RF (89%) and anti-CCP (96%). Medium or high RA activity was documented in all pts (DAS28 5, 4 [5, 0;6, 5]; SDAI 38, 9 [24, 2;42, 9], CDAI 31, 6 [20, 5; 41, 9]). None of RA pts was ever treated with either glucocorticoids (GC) or disease-modifying antirheumatic drugs (DMARD). The control group consisted of 30 healthy subjects without rheumatic diseases, matched by age and sex with RA patients. Serum concentration of adipokines (adiponectin, leptin, and visfatin) was measured with ELISA. A multiplex technology X-MAP was used to measure inflammatory cytokines (interleukins (IL) -1β, 2, 4, 5, 6, 7, 8, 9, 10, 12, 13, 15, 17). Results: Adiponectin level was higher in untreated RA patients than in the controls (23, 0 [15, 8; 67, 0] vs 9, 2 [5, 6; 12, 2]ng/ml), while leptin and visfatin concentration were lower than in the control group (25, 0 [8, 0; 32, 0] vs 30, 5 [19, 0; 46, 2]ng/ml, and 434 [336, 533] vs 753 [427;1000]ng/ml, respectively, p <0, 05 for all). Clear correlation was established between leptin and IL-4 (r=0, 39, p =0, 04), IL-17 (r=0, 4, p =0, 03), and ESR (r=0, 3, p =0, 05) levels. High visfatin concentration was associated with increased IL-5 (r=0, 4, p =0, 03), and IL-9 (r=0, 4, p =0, 04) levels. Adiponectin did not show correlation with any of these parameters. The marker of insulin resistance (leptin to adiponectin ratio) correlated with ESR (r=0, 38, p =0, 05) and CRP (r=0, 4, p =0, 04). Conclusions: Statistically significant correlation was established between some adipokines (leptin, visfatin) and Th17, Th2 cytokine levels in DMARD- and GC-naïve early RA patients. Disclosure of Interest: None declared